(3QSGdI GdeYGOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI bGd CaGV Gddg Ydi QhM GdTjN GdCej ai GdOGQ Hf CfhGQ GdMceI hWgQ faSg Yf COfGS GdWHY hBJGg ef GdHbGA eG jaj HGcJSGH s
(3BNQgG (B:s
(3hEPG GHdZfG gPG GdeHdZ adfJSe GdebGdI hdfMeO Gddg Ydi eG habfG dg ef Pdc s
(3Vef eLehY , JQJjHgG (B: 12s
(3cJHgG Edi CHj HcQ Hf eMeOs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs